Gut microbiota-derived metabolites modulate Treg/Th17 balance: novel therapeutic targets in autoimmune diseases - Li, Guolin; Xiong, Yu; Li, Zhimin; Yu, Qin; Li, Shiran; Xie, Jingxian; Zeng, Siyu; Yu, Dongke; Yang, Yong; Yu, Jiangping (Frontiers in Immunology, 2025)
Dysregulation of the homeostasis between regulatory T cell (Treg) and T helper 17 cell (Th17) is increasingly recognized as a pivotal mechanism in the pathogenesis of autoimmune diseases. Emerging evidence indicates that gut microbiota-derived metabolites, including short-chain fatty acids, secondary bile acids, and aromatic metabolites, modulate Treg/Th17 balance by shaping immune cell differentiation and function, thereby revealing novel therapeutic opportunities. This Review synthesizes recent clinical and preclinical findings on the influence of microbial communities and their metabolites on Treg/Th17 dynamics and examines the underlying mechanisms in representative autoimmune disorders, such as rheumatoid arthritis, systemic lupus erythematosus, Graves’ disease, autoimmune hepatitis, and myasthenia gravis. We critically evaluate current microbiome-targeted interventions and discuss their translational potential, highlighting both promises and challenges. Finally, we outline priorities for future research, focusing on multi-omic integration, the development of individualized therapeutic strategies, and rigorous clinical evaluation, to facilitate the development of safe and effective microbiota-based therapies for autoimmune diseases.